2002
DOI: 10.1046/j.1440-1819.2002.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for an association between the 5‐hydroxytryptamine 5‐HT2a receptor gene and schizophrenia in Kuwaiti Arabs

Abstract: The prevalence of T102C polymorphism of the 5-hydroxytryptamine 5-HT 2a receptor gene has been investigated using a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method in 80 Kuwaiti Arabs with schizophrenia and in 109 normal healthy controls with a similar ethnic background. There was no significant difference in the frequency of T102 polymorphism in the Kuwaiti cohort of schizophrenia patients and the controls (P = 0.23).The data from Kuwaiti Arabs (although our sample size is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…An over-representation of the C allele in schizophrenia patients compared with control individuals has been found in several, but not all studies, and a metaanalysis based on over 3000 subjects [22] showed a small, but highly significant, effect with no evidence of publication bias. Nevertheless, the two most recent attempts to replicate the T102C association with schizophrenia have been negative [23,24]. The larger of the two studies [23] contained just under 1000 subjects and reduced confidence in the T102C association.…”
Section: Functional Candidate Genesmentioning
confidence: 99%
“…An over-representation of the C allele in schizophrenia patients compared with control individuals has been found in several, but not all studies, and a metaanalysis based on over 3000 subjects [22] showed a small, but highly significant, effect with no evidence of publication bias. Nevertheless, the two most recent attempts to replicate the T102C association with schizophrenia have been negative [23,24]. The larger of the two studies [23] contained just under 1000 subjects and reduced confidence in the T102C association.…”
Section: Functional Candidate Genesmentioning
confidence: 99%
“…The C (A2 or 2) allele and CC (A2A2 or 2/2) genotype of the T102C polymorphism were reported to be associated with this disorder in some studies, including the original research [10] and meta-analyses [1,28]. However, there are a number of reports in which the association has not been replicated [2,4,5,7,12,14,19]. The controversial results can be partially explained by ethnic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Joober et al [1999] found that genotype A2/A2 tended to be more frequent in male patients with schizophrenia characterized by poor long-term outcome and poor response to typical neuroleptics (Bonferroni corrected P ¼ 0.09). However, the conflicting results were reported in the patients from another Japanese population [Shinkai et al, 1998], Irish [Hawi et al, 1997], Shanghai and Chengdu Chinese [He et al, 1999], Taiwan Chinese [Lin et al, 1999], Italian [Serretti et al, 2000], Hong Kong Chinese [Chen et al, 2001], Kuwaiti Arabs [Haider and Zahid, 2002], Turkish [Herken et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and the results of metaanalyzes have shown an association between the T102C polymorphism of the 5-hydroxytryptamine receptor 2A (HTR2A) gene and schizophrenia [Inayama et al, 1996;Williams et al, 1996Williams et al, , 1997Lohmueller et al, 2003]. However, many negative findings [Hawi et al, 1997;Shinkai et al, 1998;He et al, 1999;Lin et al, 1999;Serretti et al, 2000;Chen et al, 2001;Haider and Zahid, 2002;Herken et al, 2003] have also been reported.…”
Section: Introductionmentioning
confidence: 99%